Scripting Farming Simulator with Lua Unlocking the Virtual Fields - Brumbaugh, Zander; Leithner, Manuel (Apress : Imprint: Apress, 2024)
Create mods using the popular game Farming Simulator with Lua, a versatile scripting language that can run on various platforms and applications. This open access book is best suited for programmers who want to learn how to use Lua to write scripts that can enhance and extend the gameplay experience. You'll start by reviewing the basics of programming in Lua and then move on to advanced topics, such as object-oriented programming, vehicle and placeable specializations, network synchronization, and creating custom user interfaces. With step-by-step instructions and detailed explanations, you'll see how to create scripts that modify game mechanics and add new features to the game. The practical examples and projects are ideal for providing hands-on experience with Lua scripting. Whether you are a creator looking to take your skills to the next level or a game developer interested in learning a new programming language, Scripting Farming Simulator with Lua is the ultimate guide to mastering Lua scripting. You will: Implement a basic "Hello-World" mod Add a new graphical user interface to your mod Use hook scripts to extend base game features Publish your mod on the official Farming Simulator ModHub .